PELAKSANAAN KEWAJIBAN PEMELIHARAAN ANAK (ALIMENTASI) OLEH ORANG TUA PASCA PUTUSAN PERCERAIAN DI KABUPATEN ROKAN HILIR - Hanifah, Mardalena; Fitriani, Riska; ', Agen (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The obligation of parents toward children include the maintenance of the child, both parents are still intact in the bonds of marriage and those already divorced, reality although liability issues of parent against children after the divorce it has been arranged in various regulations perundang-undangan and islamic law, in Article 156 Compilation of Islamic Law on Marriage For Divorce Due to Rupture which reads mumayyiz Children who do not deserve hadhanah of her mother, unless the mother has died, children who already mumayyiz right to choose to get hadhanah of father or mother, and all costs and living hadhanah a dependent child's father according to his ability, at least until the child is an adult and can take care of themselves (21 years), but in public life still many parents, especially fathers who neglect these duties if he had been divorced by his wife / mother of his children.The purpose of this thesis is to determine how the shape of the child maintenance obligations (alimony) by parents after divorce judgment in Rokan Hilir district, to know how to remedy if the non-performance of obligations of child maintenance (alimony) by parents after divorce judgment in Rokan downstream.This study uses the Sociological Juridical for research conducted in the Religious Ujung Tanjung Rokan Hilir. Population and sample is the whole of the parties relating to the matter under investigation amounted to 3 people, the source of the data used is data, primary, secondary and tertiary, data collection technique used observation, questionnaires, interviews and review of the literature.From the discussion presented above it can be concluded that the implementation of the obligations of child maintenance (alimony) by parents after divorce judgment in Religion The court jurisdiction Ujung Tanjung Rokan Hilir not run smoothly and showed a lack of responsibility ex-husband / father of the child maintenance obligations that must be given to their children. Factors shortcomings of child maintenance obligations (alimony) by parents after divorce judgment can be grouped to four factors: the first factor of the economy, both public awareness, the third means and facilities in the implementation of law enforcement child maintenance obligations (alimony). And remedies, if not the implementation of the travel after the divorce judgment against the maintenance of the child is to execute payments.Keywords: Liability, child maintenance, post-verdict, divorce.